Efforts to Improve Long Jump Skills in Squat Style Through a Play-Based Approach on 11th Grade Science Students at Teladan High School in Sei Rampah - Muhammad Syahri; Albadi Sinulingga; Nurkadri (UNIB Press, 2023)
The problem of this research is the inadequate learning process and facilities in the long jump technique using the squat style, as well as the lack of mastery of basic skills in long jump, resulting in suboptimal student learning outcomes. Based on the problem, the research problem in this study is how to improve learning outcomes in long jump using the squat style through a play-based approach for students in class XI IPA of Teladan Sei Rampah High School, Sei Rampah Subdistrict, Serdang Bedagai District. This study is a Classroom Action Research (CAR) conducted in 2 cycles. The population and subjects of this study are 36 students in class XI IPA of Teladan Sei Rampah High School, Sei Rampah Subdistrict, Serdang Bedagai District. The results of this study show that through play-based learning, students' abilities in learning long jump using the squat style can be improved. The conclusion of this study is that through play-based learning, the ability to perform long jumps using the squat style can be improved for students in class XI IPA of Teladan Sei Rampah High School, Sei Rampah Subdistrict, Serdang Bedagai District.